Sinergi Pendampingan Ekonomi, Kesehatan, dan Hukum dalam Meningkatkan Kesejahteraan Warga Desa Lekor Janapria - Lutfiana, Lutfiana (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to explore the synergy between mentoring in the economic, health, and legal sectors to improve the well-being of the community in Lekor Village, Janapria Subdistrict, Central Lombok Regency. The mentoring activities were carried out using a participatory approach, actively involving local residents in every stage of the process. In the economic sector, the mentoring program focused on entrepreneurship training, small business management, and access to markets for local products. In terms of health, activities were directed at raising community awareness about the importance of clean and healthy living behaviors (PHBS) and improving access to basic healthcare services. Meanwhile, in the legal sector, the main focus was on educating the community about their rights, providing legal counseling, and enhancing legal awareness. The findings indicate that an integrated and sustainable approach across these three sectors can drive significant improvements in living standards, increase income, promote environmental health, and strengthen legal understanding among residents. Collaboration between village authorities, facilitators, and the community was identified as a key factor contributing to the success of the program. This study highlights the importance of strengthening local capacity and ensuring the continuity of cross-sectoral mentoring to promote inclusive and competitive village development.